Correction: Design of CO2 sorbents using functionalized fibrous nanosilica (KCC-1): insights into the effect of the silica morphology (KCC-1 vs. MCM-41). Issue 18 (25th April 2016) - Singh, Baljeet; Polshettiwar, Vivek
Abstract : Correction for 'Design of CO2 sorbents using functionalized fibrous nanosilica (KCC-1): insights into the effect of the silica morphology (KCC-1 vs. MCM-41)' by Baljeet Singh et al., J. Mater. Chem. A, 2016, DOI: 10.1039/c6ta01348a.